2021
DOI: 10.1002/saj2.20238
|View full text |Cite
|
Sign up to set email alerts
|

Application method influences the oxidation rate of biologically and chemically produced elemental sulfur fertilizers

Abstract: Elemental sulfur (ES) is commonly used as a fertilizer S source but needs to be oxidized to sulfate to become plant-available. We assessed how placement (surface applied or incorporated) affects the oxidation of ES fertilizers. The fertilizers included an ES powder, a suspension of biogenic ES particles, and three granular fertilizers: two ES-bentonite pastilles and one monoammonium phosphate fertilizer cogranulated with ES. The fertilizers were applied either on the surface (broadcast) or incorporated into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In addition, the S fertilizer type also had an important effect on SUE. Matamwa et al [46] compared the effect of SO 4 −S and elemental S on SUE in their study and found that the application of SO 4 −S, such as single superphosphate and gypsum, results in higher SUE values than the application of elemental S, due to the slow oxidation of elemental S to SO 4 −S [50,63,64]. In this study, elemental S accounted for half of the S application, which was also a significant factor contributing to the reduced SUE.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the S fertilizer type also had an important effect on SUE. Matamwa et al [46] compared the effect of SO 4 −S and elemental S on SUE in their study and found that the application of SO 4 −S, such as single superphosphate and gypsum, results in higher SUE values than the application of elemental S, due to the slow oxidation of elemental S to SO 4 −S [50,63,64]. In this study, elemental S accounted for half of the S application, which was also a significant factor contributing to the reduced SUE.…”
Section: Discussionmentioning
confidence: 99%